2011
DOI: 10.1002/hbm.21172
|View full text |Cite
|
Sign up to set email alerts
|

Seeing touch in the somatosensory cortex: A TMS study of the visual perception of touch

Abstract: Recent studies suggest the existence of a visuo-tactile mirror system, comprising the primary (SI) and secondary (SII) somatosensory cortices, which matches observed touch with felt touch. Here, repetitive transcranial magnetic stimulation (rTMS) was used to determine whether SI or SII play a functional role in the visual processing of tactile events. Healthy participants performed a visual discrimination task with tactile stimuli (a finger touching a hand) and a control task (a finger moving without touching)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 74 publications
(99 reference statements)
8
66
0
Order By: Relevance
“…Notably, the time course of TMS-induced perturbations differs between the two targets: TMS targeting OFA at 60 ms after stimulus onset maximally disrupts performance while the largest effects of S1-TMS occur with pulses delivered 130 ms after visual stimulus onset [63]. Visual processing related to non-face body parts also recruits somatosensory cortex, as online rTMS targeting S1 impairs discrimination performance in a task requiring participants to judge whether a video depicts a hand being touched [65]. Thus, somatosensory cortex may be specialized for processing body-related information across sensory modalities.…”
Section: (C) Multimodality Of Sensory Cortexmentioning
confidence: 99%
“…Notably, the time course of TMS-induced perturbations differs between the two targets: TMS targeting OFA at 60 ms after stimulus onset maximally disrupts performance while the largest effects of S1-TMS occur with pulses delivered 130 ms after visual stimulus onset [63]. Visual processing related to non-face body parts also recruits somatosensory cortex, as online rTMS targeting S1 impairs discrimination performance in a task requiring participants to judge whether a video depicts a hand being touched [65]. Thus, somatosensory cortex may be specialized for processing body-related information across sensory modalities.…”
Section: (C) Multimodality Of Sensory Cortexmentioning
confidence: 99%
“…Kowalska and Szelag (2006) found that congenitally deaf adolescents were less able to estimate temporal duration, and Bolognini et al (2011) found that deaf adults were impaired compared to hearing adults in discriminating the temporal duration of touches. Bolognini et al (2011) also provided TMS evidence that auditory association cortex was involved in temporal processing at an earlier stage for deaf participants, which correlated with their tactile temporal impairment. Finally, several studies have documented temporal sequencing deficits in deaf children (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that a higher brain system is involved in motor imagery and that sensory information could affect M1 excitability during action observation. In fact, it has been reported that a mirror neuron system that performs the cross-modal processing required to integrate visual and tactile information exists in the somatosensory area [17].…”
Section: Introductionmentioning
confidence: 99%